EPID-20. MORTALITY TRENDS IN PRIMARY MALIGNANT BRAIN AND CENTRAL NERVOUS SYSTEM TUMORS VARY BY HISTOPATHOLOGY, AGE, RACE, AND SEX. (14th November 2022) - Thierheimer, Marisa; Cioffi, Gino; Waite, Kristin; Kruchko, Carol; Ostrom, Quinn; Barnholtz-Sloan, Jill
Abstract: BACKGROUND: Primary malignant brain and other central nervous system tumors (BT) are rare cancers that have shown rising mortality rates in recent years. To elucidate potential factors involved in this rising death rate, we examined mortality trends for primary malignant BT in the United States (US) stratified by histopathology groupings, age, race, and sex. METHODS: Mortality rates for demographic factors within primary malignant BT were generated using the Center for Disease Control's National Vital Statistics Systems (NVSS) data from 2004 to 2018. Additionally, histopathology-specific incidence-based mortality rates were calculated using the National Cancer Institute's Surveillance, Epidemiology, and End-Results (SEER) 18 data from 2004 to 2018. Joinpoint modeling was used to estimate mortality trends and annual percent changes (APC) with corresponding 95% confidence intervals (CI). RESULTS: Overall, there was a very small increase in mortality from 2004-2018 (NVSS, APC: 0.3%, 95% CI: 0.1%-0.5%). Individuals 65+ years of age saw a small increase in mortality (NVSS, APC: 0.6%, 95% CI: 0.4%-0.9%), while changes in individuals of other ages were non-significant. Asian/Pacific Islander or American Indian/Alaskan Native had the largest increase in mortality (NVSS, APC: 1.6%, 95% CI: 0.7%-2.4%). Overall mortality trends by sex were similar. Among histopathology groupings, there was a small mortality increase in adults ages 65+ years with glioblastoma (SEER, APC: 0.5%, 95% CI: 0.1%-1.0%), while patients with other glioma and non-glioma did not show significant changes in mortality. In pediatric patients (ages 0-14 years), high-grade glioma mortality increased significantly from 2004-2015 (SEER, APC: 7.0%, 95% CI: 3.8%-10.3%) but had a non-significant decrease from 2015-2018. Pediatric patients with embryonal tumors had a significant mortality decrease between 2004 and 2018 (SEER, APC: -1.9%, 95% CI: -3.3%-0.5%). CONCLUSION: Examining age, race, sex, and histopathology-specific mortality at the population level can provide important information for clinicians, researchers, and aid in public health planning.